Sumberdaya Lahan Basah di Situs-Situs Masa Hindu-Buddha di Daerah Aliran Sungai Batang Ggadis dan Batang Angkola - Ery Soedewo (Berkala Arkeologi Sangkhakala, 2008)
AbstractWetland exploitation along Batang Gadis and Batang Angkola River had triggered the rise of Hindu-Buddhism influence in those area. Temples ruin in Mandailing are facts of sophisticated its civilisation